Role of mathematical modelling and applications in university service courses: an across countries study - Klymchuk, S; Zverkova, T (Horwood Publishing, 2001)
The aim of this study was to find out what university students, studying mathematics as a service course, think about the role of the mathematical modelling process and application problems in their studies. For this purpose a questionnaire was given to more than 500 students from 14 universities in 9 countries. The research was not a comparison of countries or universities: an across countries study approach was chosen to reduce the affect of differences in education systems, curricula, cultures. The results of the questionnaire were analysed and presented in the paper. In particular, an attempt was made to identify which step of the mathematical modelling process the students found most difficult.